Study of Cost-effectiveness and Safety of 0.2% Olopatadine in Comparison with Combination of 0.1% Olopatadine and 0.4% Ketorolac Eye Drops in Vernal Keratoconjunctivitis among Rural Population - Adhiti Todime; Narendar Koyagura; Krisna C. Pasula; Prasanna Vedula; Baswaraj Munge; Prashanth K. Patnaik (Pharmacology and Clinical Pharmacy Research, 2022)
The study aimed to compare the cost-effectiveness and safety of 0.2% Olopatadine with a combination of 0.1% Olopatadine and 0.4% Ketorolac eye drops in Vernal keratoconjunctivitis (VKC) among the rural population. This was a randomized, open-label, prospective study conducted on 129 patients who were diagnosed with VKC. All the patients were randomly allotted to 2 treatment groups. Group 1 received 0.2% Olopatadine eye drops/single drops/three times a day. Group 2 treated with a combination of 0.1% Olopatadine and 0.4% Ketorolac eye drops/single drops/two times a day for four weeks. The patients were advised to follow up during the study period in the second and fourth weeks. During the follow-ups, post-intervention cure rate, adverse drug reactions (ADR) monitoring, and cost-effectiveness of both the drugs were evaluated. A statistically significant (p<0.05) reduction of clinical symptoms was observed in both groups after four weeks of treatment. In 0.2% Olopatadine intervention, 9 cases of ADR were reported out of the 62 patients. Furthermore, treatment with a combination of 0.1% Olopatadine and 0.4% Ketorolac has shown 12 cases from 58 having ADR. Our study revealed that the 0.2% Olopatadine eye drops were a comparatively affordable choice since the cost was less. Therefore, 0.2% Olopatadine is considered a better drug choice in the given scenario of the rural population regarding their safety and cost-effectiveness.